Drogi afirmacji Boga (1) = The ways of affirmation of God - Zdybicka, Zofia (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The article indicates prevalent admonition to the ways of affirming God in the context of contemporary dilemmas on philosophical, theological and cultural field. It demonstrates the multifarious and interdisciplinary character of the problem as well as a multitude of approaches to God.
Keywords: teologia; filozofia; kultura